Clinical and biological characterization of skeletal muscle tissue biopsies of surgical cancer patients. Issue 6 (15th July 2019) - Anoveros‐Barrera, Ana; Bhullar, Amritpal S.; Stretch, Cynthia; Esfandiari, Nina; Dunichand‐Hoedl, Abha R.; Martins, Karen J.B.; Bigam, David; Khadaroo, Rachel G.; McMullen, Todd; Bathe, Oliver F.; Damaraju, Sambasivarao; Skipworth, Richard J.; et al.
Abstract: Background: Researchers increasingly use intraoperative muscle biopsy to investigate mechanisms of skeletal muscle atrophy in patients with cancer. Muscles have been assessed for morphological, cellular, and biochemical features. The aim of this study was to conduct a state‐of‐the‐science review of this literature and, secondly, to evaluate clinical and biological variation in biopsies of rectus abdominis (RA) muscle from a cohort of patients with malignancies. Methods: Literature was searched for reports on muscle biopsies from patients with a cancer diagnosis. Quality of reports and risk of bias were assessed. Data abstracted included patient characteristics and diagnoses, sample size, tissue collection and biobanking procedures, and results. A cohort of cancer patients ( n = 190, 88% gastrointestinal malignancies), who underwent open abdominal surgery as part of their clinical care, consented to RA biopsy from the site of incision. Computed tomography (CT) scans were used to quantify total abdominal muscle and RA cross‐sectional areas and radiodensity. Biopsies were assessed for muscle fibre area (μm 2 ), fibre types, myosin heavy chain isoforms, and expression of genes selected for their involvement in catabolic pathways of muscle. Results: Muscle biopsy occurred in 59 studies (total N = 1585 participants). RA was biopsied intraoperatively in 40 studies (67%), followed by quadriceps (26%; percutaneous biopsy) and other muscles (7%). Cancer site and stage, % of male participants, and age were highly variable between studies. Details regarding patient medical history and biopsy procedures were frequently absent. Lack of description of the population(s) sampled and low sample size contributed to low quality and risk of bias. Weight‐losing cases were compared with weight stable cancer or healthy controls without considering a measure of muscle mass in 21 out of 44 studies. In the cohort of patients providing biopsy for this study, 78% of patients had preoperative CT scans and a high proportion (64%) met published criteria for sarcopenia. Fibre type distribution in RA was type I (46% ± 13), hybrid type I/IIA (1% ± 1), type IIA (36% ± 10), hybrid type IIA/D (15% ± 14), and type IID (2% ± 5). Sexual dimorphism was prominent in RA CT cross‐sectional area, mean fibre cross‐sectional area, and in expression of genes associated with muscle growth, apoptosis, and inflammation ( P < 0.05). Medical history revealed multiple co‐morbid conditions and medications. Conclusions: Continued collaboration between researchers and cancer surgeons enables a more complete understanding of mechanisms of cancer‐associated muscle atrophy. Standardization of biobanking practices, tissue manipulation, patient characterization, and classification will enhance the consistency, reliability, and comparability of future studies.